2016
DOI: 10.1186/s12936-016-1478-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and diagnostics of congenital malaria in rural Burundi, a cross-sectional study

Abstract: BackgroundCongenital malaria, defined as the presence of asexual forms of malaria parasites in the peripheral blood during the first 7 days of life, remains a neglected area of research. Knowledge gaps exist about prevalence and management of malaria in this age group. The objective of this study was to evaluate the prevalence of congenital malaria and the validity of a rapid diagnostic test (RDT) for its diagnosis in rural Burundi.MethodsA cross-sectional study was conducted in a meso-endemic malaria context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…The first study conducted in Niger in 2000 gave a prevalence of 13.3% [ 15 ]. It was 19% in Togo with a parasite density ranging from 360 to 870 P/ μ L [ 19 ], 10% in Burkina [ 20 ], 2.2% in Ghana [ 21 ], 0.64% in Brazzaville [ 22 ], 0.03% in Mali [ 23 ], and 0% in Burundi [ 24 ]. Menendez and Mayor explain this wide variation in the prevalence of congenital malaria infection by: (I) the difference in the definition of congenital malaria, (II) the level of maternal immunity, (III) the type of blood examined (peripheral blood or the umbilical cord blood of the newborn), (IV) the expertise of microscopists, (V) the method of biological confirmation (microscopy, rapid diagnostic test, or chain polymerization reaction), and finally, (VII) the intensity of malaria transmission from the site [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first study conducted in Niger in 2000 gave a prevalence of 13.3% [ 15 ]. It was 19% in Togo with a parasite density ranging from 360 to 870 P/ μ L [ 19 ], 10% in Burkina [ 20 ], 2.2% in Ghana [ 21 ], 0.64% in Brazzaville [ 22 ], 0.03% in Mali [ 23 ], and 0% in Burundi [ 24 ]. Menendez and Mayor explain this wide variation in the prevalence of congenital malaria infection by: (I) the difference in the definition of congenital malaria, (II) the level of maternal immunity, (III) the type of blood examined (peripheral blood or the umbilical cord blood of the newborn), (IV) the expertise of microscopists, (V) the method of biological confirmation (microscopy, rapid diagnostic test, or chain polymerization reaction), and finally, (VII) the intensity of malaria transmission from the site [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence data are similar to reports in Tanzania, Burkina Faso, and Nigeria, [15][16][17] but higher than those in Burundi and the Calabar area of Nigeria. 18,19 Two studies that used polymerase chain reaction (PCR) to detect malaria parasitemia found a higher prevalence of congenital malaria but this is most likely because of the more sensitive detection method used. 20,21 Thus, these observed differences in congenital FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
“…Only two other studies have previously evaluated RDT performance to detect congenital malaria infections 37 , 38 . In Nigeria, pLDH-Optimal® RDT did not detect any congenital malaria infection while prevalence by LM was 10.9% 37 and, in Burundi two newborns were found positive by SD-Bioline Pf HRP2 but none by CareStart pan-pLDH 38 .…”
Section: Discussionmentioning
confidence: 99%